2010
DOI: 10.1186/1472-6920-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Job requirements compared to medical school education: differences between graduates from problem-based learning and conventional curricula

Abstract: BackgroundProblem-based Learning (PBL) has been suggested as a key educational method of knowledge acquisition to improve medical education. We sought to evaluate the differences in medical school education between graduates from PBL-based and conventional curricula and to what extent these curricula fit job requirements.MethodsGraduates from all German medical schools who graduated between 1996 and 2002 were eligible for this study. Graduates self-assessed nine competencies as required at their day-to-day wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
98
0
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 22 publications
7
98
0
4
Order By: Relevance
“…19 With regard to the attitude of students toward PBL, the present study indicated that students were highly motivated to learning in small groups. This finding is supported by the study findings of Schlett, et al, Maudsley, et al, and Tavakol, et al [20][21][22] Compare to LBL, PBL inflicts significant impact on how students find and use information. This is in consistent with the studies of Lorna Dodd et al 23 and Kuo-Inn Tsou, et al 24 Hwang in University of Illinois showed that PBL was more effective for improving students" knowledge and satisfactions than LBL, which is in conformity with the present study.…”
Section: Discussionsupporting
confidence: 69%
“…19 With regard to the attitude of students toward PBL, the present study indicated that students were highly motivated to learning in small groups. This finding is supported by the study findings of Schlett, et al, Maudsley, et al, and Tavakol, et al [20][21][22] Compare to LBL, PBL inflicts significant impact on how students find and use information. This is in consistent with the studies of Lorna Dodd et al 23 and Kuo-Inn Tsou, et al 24 Hwang in University of Illinois showed that PBL was more effective for improving students" knowledge and satisfactions than LBL, which is in conformity with the present study.…”
Section: Discussionsupporting
confidence: 69%
“…In Indonesia, a relatively high incidence is reported—at least 5.7 among men and 1.9 among women per 100,000 people—compared with the global incidence average of 1.9 among men and 0.8 among women for every 100,000 individuals [45]. It should be noted, however, that the actual incidence of nasopharynx cancer in Indonesia is not known owing to incomplete registration [11].…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, primary healthcare is generally handled by health centers named Puskesmas. Lack of knowledge among the general practitioners working in these centers regarding the various aspects of nasopharynx cancer, may lead to a delay in diagnosis [11]. Thus, only about 14% of patients who have metastasis at the initial diagnosis and 29% of patients without metastasis show response to therapy, about 70–95% response to therapy is good, so in general response to the therapy is poor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PBL has been widely accepted by health care educators as a pedagogical/andragogical model to promote and develop essential skills needed by 21 st -century professionals (Schlett et al, 2010;Stewart, Brown, Clavier, & Wyatt, 2011;Tavakol & Reicherter, 2003). To corroborate this, the Association of American Colleges and Universities conducted a "National Survey of Business and Nonprofit Leaders" to determine which skills employers hold in highest regard when making hiring decisions (Hart Research Associates, 2013).…”
Section: Introductionmentioning
confidence: 99%